2015
DOI: 10.1002/oby.21326
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between actigraphy‐assessed sleep quality and fat mass in college students

Abstract: Objective: Only a few studies have used objective measurements to investigate the relationship between sleep quality and obesity. These studies showed controversial results. Methods: Sleep efficiency was measured by Actiwatch 2 in 132 healthy students (age 23.3 6 3.7 years, BMI 23.1 6 4.1 kg/m 2 ) for 12 6 3 nights, differentiating between work and free days. Physical activity, dietary habits, and autonomic function (heart rate variability, HRV) were analyzed as potential determinants of sleep quality and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
2
28
0
2
Order By: Relevance
“…Moreover, although sleep quality would be an important factor to consider along with sleep duration, it could not be determined in our study because health survey questionnaires in KNAHNES IV and V did not address quality of sleep. A recent study found that low sleep quality is associated with higher fat mass among healthy college students (Kahlh€ ofer et al, 2016). Given the content of the KNAHNES IV and V data, we were only able to collect self-reported sleep hours.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although sleep quality would be an important factor to consider along with sleep duration, it could not be determined in our study because health survey questionnaires in KNAHNES IV and V did not address quality of sleep. A recent study found that low sleep quality is associated with higher fat mass among healthy college students (Kahlh€ ofer et al, 2016). Given the content of the KNAHNES IV and V data, we were only able to collect self-reported sleep hours.…”
Section: Discussionmentioning
confidence: 99%
“…Research with 4-year college students has found an association between obesity and sleep, especially for clinically obese individuals. 54,55 Indeed, obese individuals are more likely to suffer from sleep apnea that disturbs sleep patterns, suggesting that obesity causes sleep problems; however, it is equally likely that those who suffer from sleep problems also may consume more calories by virtue of being awake for more hours of the day and may expend fewer calories (since they are too tired to be physically active), suggesting that poor sleep may be a causative factor in obesity. 56 Additionally, hormones may be influencing the relationship between sleep, weight, and affect.…”
Section: Commentmentioning
confidence: 99%
“…We conceptualize sleep on a continuum, and use the term “poor sleep” to refer to shorter sleep duration, lower sleep efficiency, and longer sleep latency, as has been done in previous research (Doane and Thurston, 2014; Kahlhöfer et al, 2016). …”
Section: Introductionmentioning
confidence: 99%